Can POSSUM accurately predict post‐operative complications risk in patients with abdominal Crohn's disease?. Issue 1 (24th June 2013) - Ugolini, Giampaolo; Montroni, Isacco; Rosati, Giancarlo; Ghignone, Federico; Bacchi‐Reggiani, Maria Letizia; Belluzzi, Andrea; Castellani, Lucia; Taffurelli, Mario
Abstract Background Although the majority of patients with Crohn's disease (CD) are young, they are often seriously ill when surgery is required. The Physiological and Operative Severity Score for the enUmeration of Mortality and morbidity (POSSUM) is a risk prediction scoring system estimating 30‐day complications. The primary endpoint was to evaluate POSSUM efficacy in this subgroup. The secondary endpoint was to determine any potential correlation between POSSUM, Harvey–Bradshaw Index (HBI), length of stay (LOS) and anastomotic leak. Methods All patients affected by abdominal CD who underwent elective and emergency surgery from 2006 to 2011 were prospectively enrolled in the study. POSSUM expected morbidity and mortality were compared to the observed outcomes (O/E ratio). Logistic regression analysis was performed to evaluate POSSUM and HBI adequacy. Correlation between POSSUM, HBI, LOS and anastomotic leak was investigated with linear regression analysis. Results One hundred twenty‐three patients underwent abdominal surgery. The overall 30‐day mortality rate estimated by the Portsmouth‐POSSUM was 1.22% (95% confidence interval (CI) 0.4–3.6) while no deaths were observed (O/E = 0). The prediction regarding the post‐operative complication rate was 22.04% (95% CI 11.1–51.2) and the observed overall morbidity rate was 21.95% (O/E = 0.99). The mean HBI score was 6.85 while LOS was 9.4 days. POSSUM and HBI were found to be significant predictors of post‐operative complications at the univariate logistic regression analysis (OR 1.17 95% CI 1.06–1.30 and OR 1.25 95% CI 1.04–1.49, respectively). Linear regression analysis showed a significant correlation between POSSUM, HBI and LOS. Conclusion POSSUM is precise in predicting post‐operative complications in patients with abdominal CD. POSSUM correlates with HBI.